Rheumatic mitral aggression. Usefulness of 3D transesophageal echocardiography - Cupe-Chacalcaje, Kelly (2022)
Rheumatic heart disease is the leading cause of cardiovascular disease in young adults under 25 years of age worldwide, with the highest prevalence in low-income countries. The usual and distinctive finding of rheumatic aggression is mitral stenosis, which leads to serious cardiovascular consequences. International guidelines establish transthoracic echocardiography (TTE) as the diagnostic test for rheumatic heart disease; however, it has limitations in the measurement of planimetry and those inherent to Doppler. Transesophageal 3D echocardiography (TTE-3D) is a new modality that shows realistic images of the mitral valve and has the added value of accurately locating the plane of maximum stenosis and better determining commissural involvement.